Magnetic Skyrmions in a Thickness Tunable 2D Ferromagnet from a Defect Driven Dzyaloshinskii–Moriya Interaction. Issue 11 (3rd February 2022) - Chakraborty, Anirban; Srivastava, Abhay K.; Sharma, Ankit K.; Gopi, Ajesh K.; Mohseni, Katayoon; Ernst, Arthur; Deniz, Hakan; Hazra, Binoy Krishna; Das, Souvik; Sessi, Paolo; Kostanovskiy, Ilya; Ma, Tianping; et al.
Abstract: There is considerable interest in van der Waals (vdW) materials as potential hosts for chiral skyrmionic spin textures. Of particular interest is the ferromagnetic, metallic compound Fe3 GeTe2 (FGT), which has a comparatively high Curie temperature (150–220 K). Several recent studies have reported the observation of chiral Néel skyrmions in this compound, which is inconsistent with its presumed centrosymmetric structure. Here the observation of Néel type skyrmions in single crystals of FGT via Lorentz transmission electron microscopy (LTEM) is reported. It is shown from detailed X‐ray diffraction structure analysis that FGT lacks an inversion symmetry as a result of an asymmetric distribution of Fe vacancies. This vacancy‐induced breaking of the inversion symmetry of this compound is a surprising and novel observation and is a prerequisite for a Dzyaloshinskii–Moriya vector exchange interaction which accounts for the chiral Néel skyrmion phase. This phenomenon is likely to be common to many 2D vdW materials and suggests a path to the preparation of many such acentric compounds. Furthermore, it is found that the skyrmion size in FGT is strongly dependent on its thickness: the skyrmion size increases from ≈100 to ≈750 nm as the thickness of the lamella is increased from ≈90 nm to ≈2 µm. This extreme size tunability is a feature common to many low symmetry ferro‐ and ferri‐magnetic compounds. Abstract : The observation of skyrmions in 2D materials has opened a door to novel tunability of their magnetic structure. Here, it is shown that the chiral Néel skyrmions are stabilized in the metallic 2D ferromagnet Fe3 GeTe2, as a result of breaking of the inversion symmetry of its crystal structure that is derived from an asymmetric distribution of Fe atoms in alternate layers in the compound. It is found that the skyrmion size in this compound is strongly influenced by the sample thickness and changes from ≈100 to ≈700 nm as the sample thickness is increased from ≈90 nm to ≈2 µm.